O curso de formação de formadores da segurança pública na rede nacional de educação a distância: um estudo de caso no telecentro de Sergipe - Oliveira, João Ribeiro de (2008)
This paper aims at training of trainers of professional public safety in the National Network of Distance Education. Thus it is a historical trace of training policy for them after the promulgation of the Constitution Citizen. It aims at examining the issues around doing business with the growth of Information and Communication applied to education, especially the Internet, within the Knowledge Society. To achieve the proposed objective, research comprised literature search and fieldwork. The literature search was the removal and examination of the literature concerning the issues raised and which constitute the conceptual framework of this study and field research was conducted in virtual environment for learning the Telecentre of Sergipe, conducting an interview with the tutor and application of questionnaire to apprentices.